DAMPAK SOSIAL EKONOMI KEBERADAAN USAHA KECIL MENENGAH (UKM) KONVEKSI DI KOTA SEMARANG - Rodhiyah Rodhiyah (Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Small and Medium Enterprises (SMEs) is one of the form of strategic alternatives to support and provide the development of economy, the weakness of SMEs: capital, credibility, labor (minimum wage and social security), the high direct costs, the limited variant of effort, and the limitation of preliminary quality product. Research aims: determine perceptions and attitudes, social and economic impacts of the existence of convection in the City Semarang. Methodololgy: cross sectional, descriptive qualitative analyzed descriptively, presented in narrative form, in five SMEs convection select purposively, resources: SME owners, labor , public figures (head of RT), and community members. Results and discussion: Perceptions and attitudes from the environment mostly positive: do not feel any negative effects, SME owners are friendly, willing to socialize with their environment, respond well if there are complaints from environs residents.UKM already have License and non-formal (resident permit and “RT”), but there is a small proportion of the less support because there is less socially SME owners with the surrounding community, there are some employees who behaved arrogance by turning on the music too loud and the use of diesel machhine which cause noise (when the lights went out). Positive social impact: The owner of SMEs participating in environmental activities: giving donors, doorprize, sports uniforms, ease when residents messaging products, the negative impact: less concerned about an environmental cleanliness, noise music, the use of diesel when the power goes out, the parking of motor less attention to the environment. Positive Economic Impact: Opening recruitment of employment (women), from within and outside the SME environment, with skills and experience, recruitment via the